Thermodynamics of Nucleation of Silicon Carbide Nanocrystals during Carbonization of Porous Silicon - Yu.S. Nagornov (Журнал нано- та електронної фізики)
The formation of SiC nanocrystals of the cubic modification in the process of high-temperature carbonization of porous silicon has been analyzed. It has been shown that the surface energy of silicon nanoparticles and quantum filaments is released in the process of annealing and carbonization. The Monte Carlo simulation has shown that the released energy makes it possible to overcome the nucleation barrier and to form SiC nanocrystals.